Analysis of Insect Communities in Gmelina arborea Plantation of Different Stand Ages in Cibugel, West Java - Dewina, Restu Utari; Irawan, Afri (Jurnal Biologi Tropis, 2025)
Community timber plantation has an essential role as a source for the wood industry. One of the community timber plantations is located in Cibugel, Sumedang Regency, West Java. Lots of Gmelina arborea are planted in this community timber plantation because it does not need specific care and have a short cutting time. However, planting Gmelina in a community timber plantation leads to insect attacks on trees from different age groups, which could decrease wood production. Sustainable insect pest control efforts can be carried out by first understanding the structure of insect communities at different plant ages. Therefore, a study was conducted to compare the diversity of insect communities in plant age groups of 2, 4, and 15 years using the pitfall trap and sticky trap methods, supported by the hand searching method and microclimate data collection. In addition, plant damage caused by insects was also determined by analyzing the absolute and relative damage intensity. The results show that the dominant insect community in Gmelina age groups 2 and 15 years is Formicidae, which are generally classified as predators. Meanwhile, in the 4-year age group, the insect community was dominated by insects classified as herbivores, pests of G. arborea plants. These results align with the highest level of plant damage, namely in the 4-year age group.